Health care services delivery in Papua New Guinea : an argument for policy change : a thesis submitted in partial fulfilment of the degree of Master of Arts in Social Policy, Department of Social Policy and Social Work, Massey University at Albany, Auckland, New Zealand - Teine, Maine Iysa (Massey University, 1998)
This thesis is researched, reasoned and structured on an argument that Papua New Guinea (PNG) Health Services Delivery and Distribution are inadequate and must see appropriate policy changes, because the inadequacy is the nature of civil services which permeates key areas such as funding allocation, staffing volume, drug supplies and distribution, geographical challenges, demographic fluatuations, mission-run health centres, and government structures; an inadequacy-generating provincial political-interference demands reformulation of policies to benefit consumers rather than individual power players. Therefore, this thesis further proposes that since health services delivery is evidenced to be inefficent due to mismanagement of systems by the provincial government and lack of financial support from the National Government (bearing in mind that all social sectors' departments in Papua New Guinea - such as Education, Youth and Home Affairs, Agriculture and the like - have similar experience), an emphasis must be placed on the National Government diverting more funds into the well-being of its population, by means of purchasing more pharmaceautical supplies, increasing staffing volume, and placing specialist medical officers in all provinces in the country. This thesis concludes with key recommendations for more appropirate policy changes to the Papua New Guinea National Health Policy at the root of which lie provincial politics and financial mismanagement in the area of health care in reference to Simbu.
Keywords: Papua New Guinea; Medical care